ANALISIS PERBEDAAN TINGKAT PEMAHAMAN WAJIB PAJAK BADAN DAN FISKUS TERHADAP PENGETAHUAN UMUM PERPAJAKAN, AKUNTANSI PAJAK, PERENCANAAN DAN PENGGELAPAN PAJAK DI KPP MADYA BATAM - Yanti, Novi; Agusti, Restu; Natariasari, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study analyzes the level of understanding of the corporate taxpayer and the tax authorities on tax planning and tax evasion in the city of Batam. This study aims to determine how well the level of understanding of the corporate taxpayer and the tax authorities to the general knowledge of taxation, tax accounting, tax planning, and tax evasion. The sample in this study is the corporate taxpayer and the tax authorities who listed at KPP Madya Batam. Total processed questionnaires consisting of as many as 71 tax corporate and 20 tax authorities. Processing data using the Independent T-test. The results prove that there is no a significant difference in understanding of the general knowledge of taxation between the taxpayer and the tax authorities, but there is a significant difference in understanding of the tax accounting, tax planning and tax evasion. Level of understanding of the difference is due to the educational background, training followed, and work experience.Keywords: taxpayer, knowledge, planning, and evasion.